2007
DOI: 10.1007/s10926-007-9086-z
|View full text |Cite
|
Sign up to set email alerts
|

Basis for a Functional Capacity Evaluation Methodology for Patients with Work-related Neck Disorders

Abstract: Background Neck pain is a common musculoskeletal complaint and a relationship with reduced work-related functional capacity is assumed. A validated instrument to test functional capacity of patients with neck pain is unavailable. The objective of this study was to develop a Functional Capacity Evaluation (FCE), which is content valid for determining functional capacity in patients with work related neck disorders (WRND). Methods A review of epidemiological review literature was conducted to identify physical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Functional capacity evaluations, while employed in some occupational health services, are currently not standard practice for all physiotherapists. The purpose of functional capacity evaluations is to provide standardized, objective and unbiased information for an employer or potential employer regarding the ability of an employee to undertake the demands of the job (6). There is evidence to suggest that individual employees underestimate their actual physical capability (7), and functional capacity evaluations, therefore, can help provide an unbiased assessment of an employee's physical capabilities and enhance the physiotherapist's recommendations for fitness for work, inform vocational rehabilitation programs, and supplement the advice given by occupational health physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Functional capacity evaluations, while employed in some occupational health services, are currently not standard practice for all physiotherapists. The purpose of functional capacity evaluations is to provide standardized, objective and unbiased information for an employer or potential employer regarding the ability of an employee to undertake the demands of the job (6). There is evidence to suggest that individual employees underestimate their actual physical capability (7), and functional capacity evaluations, therefore, can help provide an unbiased assessment of an employee's physical capabilities and enhance the physiotherapist's recommendations for fitness for work, inform vocational rehabilitation programs, and supplement the advice given by occupational health physicians and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…During this visit, a second experienced examiner repeated mPDS and mcNOS assessment and performed a neck functional capacity evaluation. 40 The second examiner and patients were blinded to results of the first examination. All patients signed informed consent forms for their data to be used for research.…”
Section: Methodsmentioning
confidence: 99%
“…Of the factors at risk for neck pain, work-related physical factors play a more important role (Ariens et al, 2001). Previous studies have shown that neck pain is positively correlated with holding the neck in a flexed posture for a prolonged period of time which can cause static loading of the musculoskeletal structures (Andersen et al, 2003;Ariens et al, 2001;Ariens et al, 2002;Cagnie et al, 2007;Eltayeb et al, 2009;Mayer et al, 2012;Palmer and Smedley, 2007;Reesink et al, 2007;Waersted et al, 2010). Evidence found that working with the cervical spine in flexion may increase the risk of neck pain (Côté et al, 2008;Ranasinghe et al, 2011;Sim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Neck flexion is also related to sick leave from work caused by neck pain (Ariens et al, 2002). It should be mentioned that prolonged neck flexion in participants measured by questionnaires based on self report (Cagnie et al, 2007;Eltayeb et al, 2009;Ranasinghe et al, 2011;Reesink et al, 2007;Sim et al, 2006). Therefore, interpretation of prolonged time may be different by each person.…”
Section: Introductionmentioning
confidence: 99%